Principles and Algorithms of Neurotic Level Anxiety Disorders (Anxiety-phobic, Panic and Generalized Anxiety Disorder Psychopharmacological Treatment - T. A. Karavaeva; A. V. Vasileva; S. V. Poltorak; Y. P. Kolesova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
The article considers modern evidence based approaches to the treatment of neurotic level anxiety disorders (social phobia, anxiety and panic disorders, generalized anxiety disorder). The main treatment issues for this category of patients are presented such as principles of differentiation, integration, complexity, integrity and short-temness).Specific psychopharmacological algorithms of each kind of anxiety disorder are elaborated on the main principles of eviedence based medicine.